STRATEGI PENINGKATAN PEMANFAATAN FASILITAS DASAR DAN FUNGSIONAL PELABUHAN PERIKANAN PANTAI (PPP) TEGALSARI KOTA TEGAL - Nurdyana, Emylyani; Rosyid, Abdul; Boesono, Herry (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2013)
The success of the capture and processing and marketing of fish caught in Tegalsari Port Fishery should be supported by the provision of adequate infrastructure and basic facilities both functional and supporting facilities at the Tegalsari Port of Fisheries fishing port, it is necessary to srtategi / analysis can provide input as to the priority should be to get the development of the more leverage. This study aims to determine the condition of basic and functional facilities in the PPP Tegalsari, analyzing the utilization rate of basic and functional facilities in the PPP Tegalsari, and provide strategies to increase utilization of PPP Tegalsari. The research was conducted using descriptive method by direct observation in the field, and the respondents from those who know the exact circumstances and problems surrounding environment. As for analyzing strategies to improve utilization of the port facilities are basic and functional analysis method used and the level of utilization of SWOT analysis. Facilities at the port level utilization was found that 81.6% of land Tegalsari PPP, groove cruise 40,3%, 17,1% harbor expansive pool, pool depth port 68,75 %, 166,9% dock , TPI 75,23%, 44.33% and a parking area. Strategies to increase the utilization optimization can be done include port facilities, increase yield, type and value of production of fishing effort; maintenance and development of basic amenities, functional, and supporting PPP Tegalsari; improving the quality of human resources through training and empowerment of fishermen and baskets, Developing cooperation with industry fish processing, and the addition of environmentally friendly fishing gear in accordance with the target economically important fisheries